Role of eHealth application Oncokompas in supporting self-management of symptoms and health-related quality of life in cancer survivors: a randomised, controlled trial. Issue 1 (January 2020) - van der Hout, Anja; van Uden-Kraan, Cornelia F; Holtmaat, Karen; Jansen, Femke; Lissenberg-Witte, Birgit I; Nieuwenhuijzen, Grard A P; Hardillo, José A; Baatenburg de Jong, Robert J; Tiren-Verbeet, Nicolette L; Sommeijer, Dirkje W; de Heer, Koen; Schaar, Cees G; et al.
Summary: Background: Knowledge about the efficacy of behavioural intervention technologies that can be used by cancer survivors independently from a health-care provider is scarce. We aimed to assess the efficacy, reach, and usage of Oncokompas, a web-based eHealth application that supports survivors in self-management by monitoring health-related quality of life (HRQOL) and cancer-generic and tumour-specific symptoms and obtaining tailored feedback with a personalised overview of supportive care options. Methods: In this non-blinded, randomised, controlled trial, we recruited patients treated at 14 hospitals in the Netherlands for head and neck cancer, colorectal cancer, breast cancer, Hodgkin lymphoma, or non-Hodgkin lymphoma. Adult survivors (aged ≥18 years) were recruited through the Netherlands Cancer Registry (NCR) and invited by their treating physician through the Patient Reported Outcomes Following Initial Treatment and Long term Evaluation of Survivorship (PROFILES) registry. Participants were randomly assigned (1:1) by an independent researcher to the intervention group (access to Oncokompas) or control group (access to Oncokompas after 6 months), by use of block randomisation (block length of 68), stratified by tumour type. The primary outcome was patient activation (knowledge, skills, and confidence for self-management), assessed at baseline, post-intervention, and 3-month and 6-month follow-up. Linear mixed models (intention-to-treat) were used to assess group differences over time from baseline to 6-month follow-up. The trial is registered in the Netherlands Trial Register, NTR5774 and is completed. Findings: Between Oct 12, 2016, and May 24, 2018, 625 (21%) of 2953 survivors assessed for eligibility were recruited and randomly assigned to the intervention (320) or control group (305). Median follow-up was 6 months (IQR 6−6). Patient activation was not significantly different between intervention and control group over time (difference at 6-month follow-up 1·7 [95% CI −0·8–4·1], p=0·41). Interpretation: Oncokompas did not improve the amount of knowledge, skills, and confidence for self-management in cancer survivors. This study contributes to the evidence for the development of tailored strategies for development and implementation of behavioural intervention technologies among cancer survivors. Funding: Dutch Cancer Society (KWF Kankerbestrijding).